Clinical features of 162 fatal cases of COVID-19: a multi-center retrospective study. Issue 3 (30th September 2022) - Zhou, Xianlong; Ding, Guoyong; Fang, Qing; Guo, Jun; Yang, Luyu; Wang, Ping; Fu, Shou-Zhi; Li, Ang; Xia, Jian; Yu, Jiangtao; Xia, Jianyou; Ma, Min; et al.
Abstract: Background: The coronavirus disease 2019 (COVID-19) has affected approximately 2 million individuals worldwide; however, data regarding fatal cases have been limited. Objective: To report the clinical features of 162 fatal cases of COVID-19 from 5 hospitals in Wuhan between December 30, 2019 and March 12, 2020. Methods: The demographic data, signs and symptoms, clinical course, comorbidities, laboratory findings, computed tomographic (CT) scans, treatments, and complications of the patients with fatal cases were retrieved from electronic medical records. Results: The median patient age was 69.5 (interquartile range: 63.0–77.25) years, and 80% of the patients were over 61 years. A total of 112 (69.1%) patients were men. Hypertension (45.1%) was the most common comorbidity, while 59 (36.4%) patients had no comorbidity. At admission, 131 (81.9%) patients had severe or critical COVID-19, whereas 39 (18.1%) patients with hypertension or chronic lung disease had moderate COVID-19. In total, 126 (77.8%) patients received antiviral treatment, while 132(81.5%) patients received glucocorticoid treatment. A total of 116 (71.6%) patients were admitted to the intensive care unit (ICU), and 137 (85.1%) patients received mechanical ventilation. Most patients received mechanical ventilation before ICU admission. Approximately 93.2% of the patients developed respiratory failure or acute respiratory distress syndrome. There were no significant differences in the inhospital survival time among the hospitals ( P =0.14). Conclusion: Young patients with moderate COVID-19 without comorbidity at admission could also develop fatal outcomes. The in-hospital survival time of the fatal cases was similar among the hospitals of different levels in Wuhan.